Competence-oriented task as a means of achieving educational results in future specialists in physical education and sports - Dranyuk O.I.; Kraft N.N.; Baeva T.E. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to theoretically develop and experimentally substantiate the effectiveness of using competency-oriented tasks in pedagogical disciplines at a physical education university. Methods and structure of the study. To achieve the goal, the following methods of pedagogical research were used: analysis and synthesis of literature on the research problem, study and analysis of regulatory documents, pedagogical observations, survey in the form of conversations with colleagues and students, pedagogical experiment, methods of mathematical statistics. The study was conducted on the basis of the Department of Pedagogy of NSU. P.F. Lesgafta, St. Petersburg. Results and conclusions. The experiment conducted allows us to state the effectiveness of theoretically developed and experimentally substantiated competency-oriented tasks in pedagogical disciplines. Their use ensures that future specialists in physical culture and sports develop interdisciplinary professionally oriented knowledge, skills, and work actions that contribute to the successful implementation of labor functions, the effective monitoring of which is carried out within the framework of professionally oriented and scientific-pedagogical practices.